2016
DOI: 10.1093/cid/ciw621
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Antiretroviral Therapy Reduces Risk of Infection-Related Cancer During Early HIV Infection

Abstract: Background. In the Strategic Timing of Antiretroviral Treatment (START) study, immediate combination antiretroviral therapy (cART) initiation reduced cancer risk by 64%. We hypothesized that risk reduction was higher for infection-related cancer and determined by differences in CD4 cell counts and human immunodeficiency virus (HIV) RNA between the study arms.Methods. Incident malignancies in START were categorized into infection-related and infection-unrelated cancer. We used Cox models to assess factors assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 40 publications
7
70
1
1
Order By: Relevance
“…In the START trial, in which 4,685 HIV-positive participants with CD4 counts > 500 /μl were randomized either to start cART immediately or to defer therapy until the CD4 count dropped below 350 cells/μl, the reduced risk of infection-related cancer in the immediate arm was mainly driven by a reduction in KS incidence [11]. Similar results were seen in the SMART trial, in which patients on a CD4 T cell-guided cART strategy had a higher incidence of KS lesions during treatment interruptions than patients on continuous cART [12].…”
Section: Ks and Cartmentioning
confidence: 99%
“…In the START trial, in which 4,685 HIV-positive participants with CD4 counts > 500 /μl were randomized either to start cART immediately or to defer therapy until the CD4 count dropped below 350 cells/μl, the reduced risk of infection-related cancer in the immediate arm was mainly driven by a reduction in KS incidence [11]. Similar results were seen in the SMART trial, in which patients on a CD4 T cell-guided cART strategy had a higher incidence of KS lesions during treatment interruptions than patients on continuous cART [12].…”
Section: Ks and Cartmentioning
confidence: 99%
“…Recent randomized data indicate that cART reduces risk of KS and NHL also during early HIV infection before the development of overt immunosuppression [••46]. This benefit is measurable in the short term and reported in one trial with relatively short follow up [••46].…”
Section: Introductionmentioning
confidence: 99%
“…Recent randomized data indicate that cART reduces risk of KS and NHL also during early HIV infection before the development of overt immunosuppression [••46]. This benefit is measurable in the short term and reported in one trial with relatively short follow up [••46]. The long term effect of cART exposure on cancer risk, however, is not well defined and some cohort studies have demonstrated an independent link between long term cART exposure and cancer risk [16, ••17, •18, 47].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations